PEMBUATAN ASIMETRIK MEMBRAN SELULOSA ASETAT UNTUK PENGOLAHAN AIR : PENGARUH KONSENTRASI ZAT ADITIF TERHADAP KINERJA MEMBRAN - Aprian Indra Wibowo; Ganang Dwi Harjanto; Tutuk D. Kusworo (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2012)
Membrane is a thin layer, a barrier between two phases that are semipermeable, and serves as a selective separation media. Asymmetric membrane is a membrane that consists of three layers, they are dense layer, intermediate, and porous substructure. With that structure, asymetric membrane produce higher flux than simetric membrane. In the process of membrane manufacture, the concentration of additives that are added is important because it can affect membrane flux and rejection.. The purposes of this research are make an asymmetric membrane using cellulose acetate polymer and determine the effect of different additives concentration toward morphological structure and membrane performance. Membranes prepared by phase inversion method with a variation of the additive concentration of 2,5%, 3,5%, and 5% wt. Membranes composed of 23% CA and evaporation time used is 25 seconds. Membrane was characterized by flux, rejection, and morphological analysis using SEM. Flux and rejection were measured by brackish water as a feed. The results of FTIR analysis showed the larger absorption peaks indicates that the increasing concentrations of PEG addition make the PEG molecular weight and the unit re-CH2-CH2O- greater. The results of SEM analysis showed all the membranes that are formed has an asymmetric structure consisting of a thin fine porous structure selective barrier and sub​​-structure of the porous layer is thicker. With the presence of increasing concentrations of poly ethylene glycol, a membrane pore formed more dense. The composition of membrane showing optimal performance are 23% CA, 5% PEG, and 25 second evaporation time with flux 16,741 L.mˉ².h-1, NTU rejection 89%, TDS rejection 80%, and Ca rejection 83%.